Chromosome differentiation in three species of Leptostemonum (Solanum, Solanaceae) endemic to Oceanic Islands - Chiarini, Franco Ezequiel (2016)
The chromosomes of Solanum nelsonii, S. sandwicense (endemic to the Hawaii islands) and S. vespertilio (from the Canary islands) were studied by means of classical staining, CMA/DAPI banding and FISH with probes for the 18-5.8-26S and 5S rDNA genes. The aim of this study was to test for chromosomal changes (chromosome number, karyotype, heterochromatin pattern, rDNA loci) during the evolution of these taxa with respect to their continental relatives. An apparent chromosome stasis was confirmed in all three species, in regards to chromosome number and karyotype morphology. However, there was also evidence of cryptic, cumulative sequence changes. Speciation in these species is not likely associated with large, obvious chromosome rearrangements or polyploidy, but more likely due to genetic divergence.